MUTU ABON IKAN LAYANG (Decapterus sp.) ASAL BANDA - Naralyawan, Petronella F.; Tapotubun, Alfonsina M.; Sormin, Raja B. D (INASUA: Jurnal Teknologi Hasil Perikanan, 2024)
Fish floss is a popular fish-based processed product with high culinary value. It product is widely produced on Banda Island, Maluku Province, Indonesia, which is known as a center for traditional fish processing production. This research aims to assess the quality of fish floss made from scad fish originating from Banda Island subjectively and objectively. This research was conducted using an exploratory observation method. It began with interviewing fish floss processors, purchasing the products, and analyzing them in the laboratory. The data from the analysis were presented in the form of tables and figures. The traditional fish floss processing methods carried out by the people of Banda Island through the stages of boiling, grinding the fish meat, and finally frying. The fish floss produced tradisionally has a soft texture, delicious taste, distinctive aroma, and relatively long shelf life. The average sensory evaluation scores for scad fish floss are : color 7.3, aroma 8.06, taste 7.66, texture 8.6, with a preference level ranging from like to very much like. The objective quality of escolar fish floss includes a protein content of 19.82%, fat content of 21.53%, moisture content of 6.96%, and ash content of 4.33%.